2006
DOI: 10.1093/europace/eul003
|View full text |Cite
|
Sign up to set email alerts
|

Design and rationale of a randomized study to compare amiodarone and Class IC anti-arrhythmic drugs in terms of atrial fibrillation treatment efficacy in patients paced for sinus node disease: the PITAGORA trial

Abstract: Given the high morbidity and healthcare costs associated with AF, new therapeutic strategies are needed. The results of the PITAGORA trial may help in guiding AADs therapy and ATP programming in SND patients suffering from AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…European Society of Cardiology guidelines recommend flecainide or propafenone for the long-term control of heart rhythm in AF patients with normal left ventricular function and no structural heart disease (defined as significant LVH and myocardial ischemia). These recommendations are strongly supported by several studies confirming flecainide's efficiency and safety profile [13][14][15]. The 2019 review of the Cochrane Antiarrhythmic Drugs database, based on four randomized controlled trials (RCT) with over 511 participants, confirmed the effectiveness of chronic treatment with flecainide acetate compared to placebo or no treatment (RR 0.65).…”
Section: Long-term Rhythm Controlmentioning
confidence: 93%
“…European Society of Cardiology guidelines recommend flecainide or propafenone for the long-term control of heart rhythm in AF patients with normal left ventricular function and no structural heart disease (defined as significant LVH and myocardial ischemia). These recommendations are strongly supported by several studies confirming flecainide's efficiency and safety profile [13][14][15]. The 2019 review of the Cochrane Antiarrhythmic Drugs database, based on four randomized controlled trials (RCT) with over 511 participants, confirmed the effectiveness of chronic treatment with flecainide acetate compared to placebo or no treatment (RR 0.65).…”
Section: Long-term Rhythm Controlmentioning
confidence: 93%